Potential of Biomass and Biogas Energy Projects in the Czech Republic - Kincl, Karel (2011)
The aim of my Master Thesis is to provide the reader a holistic picture about the current situation on the renewable energy market, specifically in the area of biomass energy. Firstly, the complex research, which had been conducted by the European Union, Czech government and individual research groups, was examined to make a comprehensive overview about the Czech energy mix of renewable sources. Secondly, the biomass energy fundamentals were elaborated in more details to provide the reader solid insights into the biomass origins, methods of energy conversion as well as its current market circumstances. Next, the financing structure of biomass energy projects together with SWOT analysis on biomass was conducted based on the personal work experience from the Department of Renewable Energy Financing at xxxxxxxxxx bank and the available analytical materials. Consequently, the recommendations for potential biomass investors were concisely described together with the market prediction and possible outlook that was suggested based on the previous analysis.